Representation of Pre-Christian Baltic Religion in the Balts’ Road Tourism Route in Lithuania and Latvia - Strmiska, Michael (The international journal of religious tourism and pilgrimage, 2023)
The Balts’ Road tourism route in Latvia and Lithuania is an interesting example of how religious tourism may be packaged within a framework of cultural heritage tourism. The Balts’ Road offers travellers insight into the medieval Baltic world before the coming of Christianity. In this context, pre-Christian religious beliefs and practices constitute but one dimension of the historical tableau that the tourism route is intended to conjure. This article examines the manner in which the pre-Christian Baltic religion is represented on the Balts’ Road, displaying a certain ambivalence that seems related to the past religious history and current religious power relations in the region.